Review of the Second International Conference «World Medicine in Everyday Practice» - I. V. Kovaleva; N. D. Fomenko (Лечащий Врач)
From April 22 to 23, 2021, the II International Scientific and Practical Conference from the cycle «World Medicine in Everyday Practice: Another Year of the Pandemic and New Challenges for the Health Service» was held online. The online broadcast of the conference was held in several time zones with the participation of 20 speakers from nine countries of the world, and its listeners were 38,5 thousand doctors from Europe and Asia. The conference focused on news about the COVID-19 pandemic, as well as observing how it is changing daily clinical practice and what challenges it poses for doctors.